Dead for a spell : a Bram Stoker mystery - Buckland, Raymond (Bram Stoker mystery, 2014)
"March 1881. The Lyceum is abuzz with the news that American actor Edwin Booth is going to be sharing the stage with their own Shakespearean star, Henry Irving. But stage manager Harry Rivers has other matters preoccupying him. One of the regular actresses has disappeared, and after a disturbing tarot card reading, Harry's boss, Bram Stoker, is convinced that something wicked is coming their way. When the poor girl's body is found, Stoker's suspicions prove to be founded--the murder scene is riddled with strange clues that Stoker recognizes as the trappings of an occult ritual. Someone is conjuring up a pernicious plot against cast and crew of the Lyceum, and if Harry doesn't track down the slaying sorcerer quickly, it could spell disaster for those he holds dearest.."--